2022
DOI: 10.51847/xasznvaqep
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Adverse Effects of Dental Bleaching with 10-16% vs. 30-37% Carbamide Peroxide: A Systematic Review

Abstract: Bleaching one's teeth is a less invasive alternative to getting aesthetic related work done. Although bleaching is safe when in contact with teeth and related tissues, some are still worried about its potential side effects. It is stated that the bleaching procedure must be employed according to a particular diagnostic, taking into consideration various aspects such as the following: kind of discoloration, condition of teeth produced by food, quantity of reagents used, age, kind of reactions to chemical compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, Alrashoud et al (2022) have reported that different concentrations of carbamide peroxide can lead to different levels of peroxide leakage, suggesting that saturation effects may occur at higher concentrations [18]. Santana et al (2021) have noted that enamel opacity increase due to HP action is a signi cant factor in the bleaching effect, which could explain why increasing concentrations beyond 16% may not enhance e cacy proportionally [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Alrashoud et al (2022) have reported that different concentrations of carbamide peroxide can lead to different levels of peroxide leakage, suggesting that saturation effects may occur at higher concentrations [18]. Santana et al (2021) have noted that enamel opacity increase due to HP action is a signi cant factor in the bleaching effect, which could explain why increasing concentrations beyond 16% may not enhance e cacy proportionally [19].…”
Section: Discussionmentioning
confidence: 99%